The Impact of Ulcerative Colitis is Greater in Unmarried and Young Patients - Robert G Maunder; Gordon R Greenberg; William J Lancee; A Hillary Steinhart; Mark S Silverberg (Canadian Journal of Gastroenterology)
GOALS: To determine whether the perceived impact of ulcerative colitis (UC) on activities of living (illness intrusiveness) is greater for people who are not living in a married or common-law relationship.